Effectiveness of Resam Fern Leaves Extract (Gleichenia linearis) as Bioinsecticide on Mortality of Black Ant (Dolichoderus thoracicus) - Chandra Halim; Wahdana Apriyani; Reh Desiva Christima Br Ginting; Dita Ariyani; Amirul Mirdas (Nusantara Scientific Medical, 2022)
Insecticides are type of pesticide used to eradicate or control pests. Generally, there are two types of insecticides, namely natural and synthetic insecticides. Natural insecticides are scarce due to their inability to eradicate pests such as black ants. Meanwhile, the use of synthetic insecticides is very practical and fast but can cause pollution that is harmful to humans, animals and other living things. Thus, natural insecticides are needed that can eradicate black ants effectively and efficiently and do not pollute the environment or poison other organisms. The research method used is combination of experimental methods, observation, and literature studies. In determining the best insecticide variation for mortality, a black ant mortality rate was measured using timer for 50 black ants. After the data was obtained, it was analyzed descriptively to determine the value of the mortality rate for each experimental sample. Based on the data obtained, the best variation of natural insecticides was the control variation of fern leaf extract with 3.646 seconds per ant. This is because fern leaf extract in insecticides contains tannin compounds which have several benefits as active pesticide ingredients. Thus, fern insecticides are effective in exterminating black ants.